USING PQRST METHOD TO IMPROVE STUDENTS’ READING COMPREHENSION - Amalia, Rizki; Marhum, Mochtar; Rita, Ferry (Tadulako University, 2023)
This research aims to determine whether using the PQRST method can improve the reading comprehension of the tenth-grade students at SMA Negeri 1 Tolitoli. The researchers applied a quasi-experimental research design by using non-random sampling techniques to get the sample. The instruments of data collection were pre-test and post-test. The pre-test was used to measure the students' prior knowledge, and the post-test was used to measure the improvement in students' reading comprehension using the PQRST method after the treatment. The t-test was analyzed to compare the mean scores of the experimental group (93.95) and the control group (89.58). The significance level was 0.05 with 60 degrees of freedom (df=66). The result of data analysis indicates that the t-counted (2,92) is higher than the t-table (1.659). It means that the hypothesis is accepted. It was concluded that using the PQRST method can improve students' reading comprehension of the tenth-grade students at SMA Negeri 1 Tolitoli.